Space experiment TUS on board the Lomonosov satellite as pathfinder of JEM-EUSO - Adams, J. H. (2015)
Space-based detectors for the study of extreme energy cosmic rays(EECR) are being prepared as a promising new method for detecting highest energy cosmic rays. A pioneering space device - the "tracking ultraviolet set-up" (TUS) - is in the last stage of its construction and testing. The TUS detector will collect preliminary data on EECR in the conditions of a space environment, which will be extremely useful for planning the major JEM-EUSO detector operation.